Primary Health Care in context with the plurality in the care of people with tuberculosis - Edna Ferreira Santos; Fátima Teresinha Scarparo Cunha; Pedro Fredemir Palha; Afranio Lineu Kritski (Revista Latino-Americana de Enfermagem)
Objective: to analyze the plurality of care provided to individuals with tuberculosis in Primary Health Care services in Rio de Janeiro, RJ, Brazil. Method: this qualitative study was conducted from 2017 to 2021. Discourse Analysis was adopted as the theoretical-methodological framework. Semi-structured interviews were conducted with service managers, healthcare professionals, and patients. The interviews were categorized using ATLAS.ti 8. The theoretical contributions of public space, plurality, and natality, as discussed by Hannah Arendt, were used to anchor the Discursive Formations on the health field. Results: the discourses revealed the complexity and challenges of organizing and implementing care practices among individuals with tuberculosis, highlighting the relevance of considering the historical, social, and individual contexts of managers, patients, and healthcare professionals. Difficulties were found in the operationalization of Health Care Networks and in searching for the patients’ uniqueness. Conclusion: an ongoing dispute was found in the interactions between Primary Health Care and the National Tuberculosis Control Program, between policies that value plurality, organize Health Care Networks, and consider democratic rights in public spaces.